1999
DOI: 10.1103/physrevlett.82.359
|View full text |Cite
|
Sign up to set email alerts
|

Universal Mechanism for Gas Adsorption and Electron Trapping on Oxidized Silicon

Abstract: We report that common gases (such as He, Ar, H 2 , O 2 , N 2 , CO) experience adsorption at oxidized silicon surfaces at 300 K via electrostatic coupling. This is deduced using contact potential measurements of the work function for gas pressure in the range 10 23 , P , 10 2 Torr. The adsorption can be enhanced through surface charging via internal photoemission of electrons leading to mutual electron-gas transient trapping. A simple electrostatic model based on monopole-dipole coupling results in an isotherm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 9 publications
1
30
0
Order By: Relevance
“…However, the electric field on real oxide surfaces is not completely screened due to (a) the discrete nature of the interface charge, (b) the possible presence of additional discrete static charges in the oxide, and (c) the fundamental fact that the oxide is amorphous with varying local electrical properties. [1][2][3][4][5][6] We now study these electric fields, and their effect on adsorbed PbSe nanocrystals, using a direct imaging method: electrostatic force microscopy (EFM). We also photoexcite the samples in order to vary the surface charge distribution.…”
Section: Introductionmentioning
confidence: 99%
“…However, the electric field on real oxide surfaces is not completely screened due to (a) the discrete nature of the interface charge, (b) the possible presence of additional discrete static charges in the oxide, and (c) the fundamental fact that the oxide is amorphous with varying local electrical properties. [1][2][3][4][5][6] We now study these electric fields, and their effect on adsorbed PbSe nanocrystals, using a direct imaging method: electrostatic force microscopy (EFM). We also photoexcite the samples in order to vary the surface charge distribution.…”
Section: Introductionmentioning
confidence: 99%
“…3, the increased concentration of the molecules on the surface of the supercharged particles is strongly dependent on the dipole moment of the molecules. In this case, the calculated concentration of molecules with large dipole moments exceeds the maximum permissible concentration n lim ( [20,33,34] the adsorption of the non-polar molecules and atoms on the thin films charged by electrons was observed experimentally. Thus, in the work of Shamir et al [33,34] such effect was observed on the silicon surfaces for Не, Ar, N 2 , O 2 , etc., and Lu [20] showed the similar effect on a thin ice surface for CCl 4 molecules.…”
Section: Dipole Interaction and Chemical Reactions On The Surface Of mentioning
confidence: 85%
“…In this case, the calculated concentration of molecules with large dipole moments exceeds the maximum permissible concentration n lim ( [20,33,34] the adsorption of the non-polar molecules and atoms on the thin films charged by electrons was observed experimentally. Thus, in the work of Shamir et al [33,34] such effect was observed on the silicon surfaces for Не, Ar, N 2 , O 2 , etc., and Lu [20] showed the similar effect on a thin ice surface for CCl 4 molecules. Also, in the Lu's experiment [20] the simultaneous decomposition of a part of the CCl 4 molecules was observed as a result of the electron capture by these molecules.…”
Section: Dipole Interaction and Chemical Reactions On The Surface Of mentioning
confidence: 85%
“…2,[36][37][38] Heating effects can alter the efficiency with which a surface generates pp-SHG, 2 but this does not account for all observations. The mechanism proposed by Mihaychuk and coworkers involves electron transport through the thin oxide overlayer, combined with trapping at the free surface mediated by oxygen in the ambient atmosphere.…”
Section: Discussionmentioning
confidence: 99%